(untitled) - Pecháček, Stanislav (Aura musica, 2019)
In his article Jiří Teml and His Compositions for Mixed Choirs, Stanislav Pecháček provides us with a clear overview of Jiří Teml's life destinies and his work for mixed choirs. The pieces are arranged in a chronological order and besides basic factual datas (the year of their origin, authors of texts, titles of individual parts, edition) the musical characteristic is provided.
Keywords: Jiří Teml; choral pieces; mixed choir